Elevated Glutathione Is Not Sufficient to Protect against Doxorubicin-Induced Nuclear Damage in Heart in Multidrug Resistance–Associated Protein 1 (Mrp1/Abcc1) Null Mice - Deng, Jun (J Pharmacol Exp Ther, 2015)
Cardiotoxicity is a major dose-limiting adverse effect of doxorubicin (DOX), mediated in part by overproduction of reactive oxygen species and oxidative stress. Abcc1 (Mrp1) mediates the efflux of reduced and oxidized glutathione (GSH, GSSG) and is also a major transporter that effluxes the GSH conjugate of 4-hydroxy-2-nonenal (HNE; GS-HNE), a toxic product of lipid peroxidation formed during oxidative stress. To assess the role of Mrp1 in protecting the heart from DOX-induced cardiac injury, wild-type (WT) and Mrp1 null (Mrp1(−/−)) C57BL/6 littermate mice were administered DOX (15 mg/kg) or saline (7.5 ml/kg) i.v., and heart ventricles were examined at 72 hours. Morphometric analysis by electron microscopy revealed extensive injuries in cytosol, mitochondria, and nuclei of DOX-treated mice in both genotypes. Significantly more severely injured nuclei were observed in Mrp1(−/−) versus WT mice (P = 0.031). GSH and the GSH/GSSG ratio were significantly increased in treatment-naïve Mrp1(−/−) versus WT mice; GSH remained significantly higher in Mrp1(−/−) versus WT mice after saline and DOX treatment, with no changes in GSSG or GSH/GSSG. GS-HNE, measured by mass spectrometry, was lower in the hearts of treatment-naïve Mrp1(−/−) versus WT mice (P < 0.05). DOX treatment decreased GS-HNE in WT but not Mrp1(−/−) mice, so that GS-HNE was modestly but significantly higher in Mrp1(−/−) versus WT hearts after DOX. Expression of enzymes mediating GSH synthesis and antioxidant proteins did not differ between genotypes. Thus, despite elevated GSH levels in Mrp1(−/−) hearts, DOX induced significantly more injury in the nuclei of Mrp1(−/−) versus WT hearts.